Host behaviour–parasite feedback: an essential link between animal behaviour and disease ecology - Ezenwa, Vanessa O. (Proc Biol Sci, 2016)
Animal behaviour and the ecology and evolution of parasites are inextricably linked. For this reason, animal behaviourists and disease ecologists have been interested in the intersection of their respective fields for decades. Despite this interest, most research at the behaviour–disease interface focuses either on how host behaviour affects parasites or how parasites affect behaviour, with little overlap between the two. Yet, the majority of interactions between hosts and parasites are probably reciprocal, such that host behaviour feeds back on parasites and vice versa. Explicitly considering these feedbacks is essential for understanding the complex connections between animal behaviour and parasite ecology and evolution. To illustrate this point, we discuss how host behaviour–parasite feedbacks might operate and explore the consequences of feedback for studies of animal behaviour and parasites. For example, ignoring the feedback of host social structure on parasite dynamics can limit the accuracy of predictions about parasite spread. Likewise, considering feedback in studies of parasites and animal personalities may provide unique insight about the maintenance of variation in personality types. Finally, applying the feedback concept to links between host behaviour and beneficial, rather than pathogenic, microbes may shed new light on transitions between mutualism and parasitism. More generally, accounting for host behaviour–parasite feedbacks can help identify critical gaps in our understanding of how key host behaviours and parasite traits evolve and are maintained.